Pengaruh Kesiapan SDM dan Sarana Prasarana terhadap Penerapan Inaportnet di Kantor Unit Penyelenggara Pelabuhan Kelas III Telaga Biru - Atika Nur Syaharani; Otri Wani Sihaloho; Femmy Asdiana; Romanda Annas Amrullah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of human resource readiness and infrastructure on the implementation of Inaportnet and to identify efforts to improve human resource readiness and infrastructure by UPP Class III Telaga Biru Office. The research population consisted of 45 individuals, including Inaportnet operators and service users, with a sample of 40 selected using Slovin’s formula. The study employed a Mixed Methods approach, with quantitative analysis using Likert scales, instrument tests, multiple linear regression, coefficient of determination (R²), and hypothesis testing, alongside qualitative analysis through data reduction, data presentation, and conclusion drawing. The results indicate that human resource readiness and infrastructure have a positive and significant joint effect on Inaportnet implementation, with a coefficient of determination of 62.2%. Efforts to enhance human resource readiness include training, user socialization, and central coordination, while infrastructure improvements involve PLN communication, generator provision, internet connectivity enhancement, and administrative device support. Consequently, obstacles in Inaportnet implementation can be minimized, supporting more effective port services.